Cadmium influences the litter decomposition of Solidago canadensis L. and soil N-fixing bacterial communities. (May 2020) - Wang, Congyan; Wei, Mei; Wang, Shu; Wu, Bingde; Du, Daolin
Abstract: It is important to illuminate the effects of litter decomposition of invasive alien species on soil N-fixing bacterial communities (SoNiBa), especially under heavy metal pollution to better outline the mechanisms for invasion success of invasive alien species. This study attempts to identify the effects of litter decomposition of Solidago canadensis L. on SoNiBa under cadmium (Cd) pollution with different concentrations (i.e., low concentration, 7.5 mg/kg soil; high concentration, 15 mg/kg soil) via a polyethylene litterbags-experiment. Electrical conductivity and total N of soil were the most important environmental factors for determining the variations of SoNiBa composition. S. canadensis did not significantly affect the alpha diversity of SoNiBa but significantly affect the beta diversity of SoNiBa and SoNiBa composition. Thus, SoNiBa composition, rather than alpha diversity of SoNiBa, was the most important determinant of the invasion success of S. canadensis . Cd with 15 mg/kg soil did not address distinct effects on alpha diversity of SoNiBa, but Cd with 7.5 mg/kg soil noticeably raised the number of species and species richness of SoNiBa mainly due to the hormonal effects. The combined S. canadensis and Cd with 15 mg/kg soil obviously decreased cumulative mass losses and the rate of litter decomposition ( k ) of S. canadensis, but the combined S. canadensis and Cd with 7.5 mg/kg soil evidently accelerated cumulative mass losses and k of S. canadensis . Thus, Cd with 7.5 mg/kg soil can accelerate litter decomposition of S. canadensis, but Cd with 15 mg/kg soil can decline litter decomposition of S. canadensis . Graphical abstract: Image 1 Highlights: S. canadensis did not affect alpha diversity of soil N-fixing bacterial communities. Cd with 7.5 mg/kg soil raises alpha diversity of soil N-fixing bacterial communities. Cd with 7.5 mg/kg soil enhances litter decomposition of S. canadensis. Cd with 15 mg/kg soil declines litter decomposition of S. canadensis.